Characterization of aromaticity in analogues of titan's atmospheric aerosols with two-step laser desorption ionization mass spectrometry. (15th October 2016) - Mahjoub, Ahmed; Schwell, Martin; Carrasco, Nathalie; Benilan, Yves; Cernogora, Guy; Szopa, Cyril; Gazeau, Marie-Claire
Abstract: The role of polycyclic aromatic hydrocarbons (PAH) and Nitrogen containing PAH (PANH) as intermediates of aerosol production in the atmosphere of Titan has been a subject of controversy for a long time. An analysis of the atmospheric emission band observed by the Visible and Infrared Mapping Spectrometer (VIMS) at 3.28 µm suggests the presence of neutral polycyclic aromatic species in the upper atmosphere of Titan. These molecules are seen as the counter part of negative and positive aromatics ions suspected by the Plasma Spectrometer onboard the Cassini spacecraft, but the low resolution of the instrument hinders any molecular speciation. In this work we investigate the specific aromatic content of Titan's atmospheric aerosols through laboratory simulations. We report here the selective detection of aromatic compounds in tholins, Titan's aerosol analogs, produced with a capacitively coupled plasma in a N2 :CH4 95:5 gas mixture. For this purpose, Two-Step Laser Desorption Ionization Time-of-Flight Mass Spectrometry (L2DI-TOF-MS) technique is used to analyze the so produced analogs. This analytical technique is based on the ionization of molecules by Resonance Enhanced Multi-Photon Ionization (REMPI) using a λ =248 nm wavelength laser which is selective for aromatic species. This allows for the selective identification of compounds having at least one aromatic ring. Our experiments show that tholins contain a trace amount of small PAHs with one to three aromatic rings. Nitrogen containing PAHs (PANHs) are also detected as constituents of tholins. Molecules relevant to astrobiology are detected as is the case of the substituted DNA base adenine. Highlights: We investigate the aromaticity in analogs of Titan's aerosols (tholins). Tholins produced by RF plasma discharge in N2 -CH4 are analyzed by L2DI-MS. Selective detection of aromatic molecules using 248 nm UV laser. We show that tholins contain a trace amount of small PAHs with one to three rings. We propose a tentative assignment of observed mass peaks to PAH and PANH's.